Nutritional Values of Foxtail Millet (Setaria italica) and other Millets Used for Common Diseases and Management - Maharajan, Theivanayagam; Duraipandiyan, Veeramuthu; Krishna, Thumadath P. A.; Soosaimanickam, Mariapackiam (Current Nutrition & Food Science, 2024)
The ever-increasing population and malnutrition in tropical and sub-tropical countries upsurge the demand and security for poor people’s food and nutrition. In erratic climatic conditions, millets can survive as they require less water, short cultivation period and are somewhat tolerant to biotic (bacteria and fungi) and biotic stresses (drought, salinity, nutrient deficiency, etc). Millets possess several nutrient rich components and several health benefits. Despite having superior nutritional, health and agricultural advantages, millets have not received their due attention. Among the millets, foxtail millet is one of the major millets in terms of its second in global production and millets’ yield, quality, and quantity are affected by various diseases. This review provides an overview of the origin and distribution of eight millets, their morphological characteristics with chemical composition, potential health benefits and the fungal, bacterial and viral diseases affecting the growth and yield of millets and their effective management in the framework of ensuring food and nutritional securities in the tropical and sub-tropical countries.
Keywords: millet diseases